HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU PEMILIHAN SKINCARE MELALUI MEDIA SOSIAL PADA PERTUKARAN MAHASISWA - Pinondang Hotria Siregar; Melva Epy Mardiana Manurung; Gabriela S.Y. Simangunsong (Jurnal Keperawatan Abdurrab, 2026)
Background Skincare is used to cleanse and care for the skin. When choosing and using skincare products, some people have poor attitudes and behaviours because they only rely on social media, advertisements, and information from friends that has not been proven to be true according to their individual skin conditions, causing various skin problems. Technology and the development of the internet make it easy to find information about skincare products to buy and use. Research Objectives To identify the description of knowledge, attitudes, and behaviours and to prove the existence or absence of a relationship between knowledge and attitudes towards facial skincare selection behaviour through social media among participants of the Merdeka Student Exchange (MSE) Batch 4 at the University of 17 August 1945 Jakarta (UTA'45 Jakarta). Research Type This study used a descriptive analytical design with a cross-sectional approach. The instrument used was a questionnaire. The sample consisted of 80 students who met the inclusion criteria. The sampling technique used purposive sampling. Research Results Bivariate analysis using the chi-square test found a relationship between knowledge and facial skincare selection behaviour through social media with a significance value of 0.000 (p<0.05) and a relationship between attitude and facial skincare selection behaviour through social media with a significance value of 0.001 (p<0.05). Conclusion There is a relationship between knowledge and attitude towards facial skincare selection behaviour through social media among participants of the Merdeka Student Exchange (MSE) Batch 4 at the University of 17 August 1945 Jakarta (UTA'45 Jakarta).